Bats diversity and composition in montane forest of Pampa Hermosa National Sanctuary, Junin, Peru - Arias, Edith (2016)
The Pampa Hermosa national sanctuary (SNPH) is an important area because it preserves relict montane forests of the Peruvian central Yungas where studies of bat’s diversity are scarce. Our objective was to document the species diversity and composition of bats communities in Pampa Hermosa and make comparisons with other Peruvian Yungas forests ranging between 1200-2000 m. We sampled four localities: Podocarpus (1900 m), Los Cedros (1600 m), Santa Isabel (1450 m) and Nueva Italia (1370 m) by using 560 mist-nights. Our results show 36 species distributed in families Phyllostomidae (30 spp.), Vespertilionidae (5 spp.) and Molossidae (1 sp.). According to the estimators Chao 1 and Chao 2, we found 77% and 42% of the species in the study area, respectively. The rank-abundance curves point to Carollia brevicauda as the most abundant in all localities; abundance of Vampyressa melissa is highlighted in Los Cedros and Podocarpus. There is a significant inverse relationship between species richness and elevation (r = -0.90, P = 0.014). Altitudes of 1200-1600 m show a species richness (35 spp.) higher than other Yungas forests, and a greater similarity to those in Manu (Ij = 0.59); on the other hand, richness at altitudes of 1600-2000 (14 spp.) was the second highest after Manu (21 spp.) and more similar to San Ramon (Ij = 0.30). Values of complementarity were higher between Pampa Hermosa and other forests in the Peruvian Yungas, ranging from 55-76% (1200 – 1600 m) to 70-83% (1600 – 2000 m). These results indicate there is a high β diversity in the bat communities from the Peruvian Yungas; however, we have to take into account the disparate sampling efforts among the evaluated localities and that additional research in areas of the SNPH not yet explored must give a stronger support to our results.